Seismic Assessment and Retrofit of Reinforced Concrete Structures - Rossi, Pier Paolo; Bosco, Melina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Many constructions are built with reinforced or prestressed concrete, and most of them are designed or expected to resist earthquake actions in addition to gravity loads. To limit the effects of seismic events on reinforced or prestressed concrete structures, many attempts have been made by researchers in order to (i) improve the knowledge of the response of materials (steel bars and concrete) and members by means of laboratory tests, (ii) develop numerical and capacity models, (iii) enhance procedures for the dynamic analysis and assessment of the seismic performance of structures and (iv) suggest innovative interventions for the seismic retrofit of old and damaged reinforced or prestressed concrete structures. This Special Issue is a collection of 11 important research works that cover a wide range of problems related to the previously mentioned research fields. Both researchers and practical engineers are expected to greatly benefit from this Special Issue in view of their own work and for a better comprehension of the response of r.c. members and structures.